Expenditure Assessment Tool - Liu, Candice (Technical Notes and Manuals; Technical Notes and Manuals ;, 2017)
This manual presents the Expenditure Assessment Tool (EAT), which helps assess expenditures for any specific country. EAT uses the commonly available software program Excel and has been designed by Expenditure Policy Division at Fiscal Affairs Department at IMF. The information EAT provides can be very useful in the evaluation of government spending and in the identification of areas where there may be room to increase spending efficiency or rationalize spending. The evaluation is done through benchmarking of spending-levels, composition and outcomes-against regional and income comparators. The focus is on both the economic and functional classification of expenditures. The application of the tool to spending in Argentina is presented as an illustration.